2010
DOI: 10.1038/hr.2010.1
|View full text |Cite
|
Sign up to set email alerts
|

Heme-arginate suppresses phospholipase C and oxidative stress in the mesenteric arterioles of mineralcorticoid-induced hypertensive rats

Abstract: Induction of heme-oxygenase (HO) is an important cellular defense mechanism against oxidative and inflammatory insults. We analyzed the effects of the HO inducer, heme-arginate, on the phospholipase C (PLC)/inositol-triphosphate (IP 3 ) pathway in the mesenteric arterioles of uninephrectomized (UnX) deoxycorticosterone acetate (DOCA)-salt hypertensive rats, which is a volumeoverload model characterized by elevated endothelin (ET-1) and mineralocorticoid-induced oxidative/inflammatory insults. Our study include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Perirenal fat HO-1 concentration was determined by enzyme-linked immunosorbent assay (ELISA) (EKS-810A, Stressgen-Assay Design, Ann Arbor, MI, USA) according to the manufacturer’s instructions as we previously reported [34], [38], [39].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perirenal fat HO-1 concentration was determined by enzyme-linked immunosorbent assay (ELISA) (EKS-810A, Stressgen-Assay Design, Ann Arbor, MI, USA) according to the manufacturer’s instructions as we previously reported [34], [38], [39].…”
Section: Methodsmentioning
confidence: 99%
“…Perirenal fat ET-1 was determined by EIA (Cayman Chemical, Ann Arbor, MI, USA) as we previously reported [38], [39]. This immunometric assay is based on a double-antibody ‘sandwich’ technique that detects ET-1 within the range of 0–250 pg/ml.…”
Section: Methodsmentioning
confidence: 99%
“…Induction of HO‐1 protects the liver from excessive formation of inflammatory cytokines (Yeligar et al, ). Induction of HO‐1 is an important cellular defence mechanism against oxidative stress (Ndisang and Jadhav, ) and is a possible risk factor in tumour development (Liu et al, ; Ku et al, ; Yao et al, , ). The role of HO‐1 in regulating cellular growth and proliferation seems to be mediated via its anti‐apoptotic and pro‐angiogenic properties (Lee et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that presence of Hcy in atherosclerotic plaque can recruit macrophages, induce M0 macrophages to M1 (pro-inflammatory) polarization, increase inflammatory response, and induce macrophage mitochondrial damage and apoptosis, and finally lead to the formation of LRNC ( 27 ). Furthermore, hypertension can trigger or induce loss of vasomotor activity, perpetuate endothelial damage which might contribute to the inflammation and formation of foam cells in atherosclerotic plaque, thus indirectly enhance the opportunity of formation of LRNC ( 28 31 ). Hence, both high levels of Hcy in serums and hypertension can accelerate the progression of LRNC in carotid atherosclerotic plaque either by the indirect or direct pathway of pro-inflammatory.…”
Section: Discussionmentioning
confidence: 99%